2012
DOI: 10.3390/ma5081462
|View full text |Cite
|
Sign up to set email alerts
|

Replication of Holograms with Corn Syrup by Rubbing

Abstract: Corn syrup films are used to replicate holograms in order to fabricate micro-structural patterns without the toxins commonly found in photosensitive salts and dyes. We use amplitude and relief masks with lithographic techniques and rubbing techniques in order to transfer holographic information to corn syrup material. Holographic diffraction patterns from holographic gratings and computer Fourier holograms fabricated with corn syrup are shown. We measured the diffraction efficiency parameter in order to charac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 27 publications
(43 reference statements)
0
3
0
Order By: Relevance
“…When the egg albumin/glucose blend was used, the value of E max = 44% was achieved [18]. In another article [19], embossed holograms were obtained on the surface of corn syrup, with G values ranging from 0 to 3000 grooves/mm. It was shown that with increasing G values, the diffraction efficiency of holograms decreases linearly.…”
Section: Introductionmentioning
confidence: 99%
“…When the egg albumin/glucose blend was used, the value of E max = 44% was achieved [18]. In another article [19], embossed holograms were obtained on the surface of corn syrup, with G values ranging from 0 to 3000 grooves/mm. It was shown that with increasing G values, the diffraction efficiency of holograms decreases linearly.…”
Section: Introductionmentioning
confidence: 99%
“… 22 Therefore, a lithographic rubbing technique was used to create phase or amplitude relief holograms in corn syrup, with a diffraction efficiency of 8.4% when using an amplitude mask or 36% when using a relief mask, all without the use of any photosensitive salts or dyes. 23 Moreover, many different nanomanufacturing techniques can be used to create holographic interference patterns. E-beam lithography was used to create computer-generated holograms.…”
mentioning
confidence: 99%
“…However, there are some indications that potassium dichromate may be toxic to human or animal health, rendering the holograms inedible . Therefore, a lithographic rubbing technique was used to create phase or amplitude relief holograms in corn syrup, with a diffraction efficiency of 8.4% when using an amplitude mask or 36% when using a relief mask, all without the use of any photosensitive salts or dyes . Moreover, many different nanomanufacturing techniques can be used to create holographic interference patterns.…”
mentioning
confidence: 99%